OHP-075 The Cost of Managing Intracranial Aneurysms by Embolization in Morocco. (12th March 2013) - Cheikh, A; Ahid, S; Abbadi, N El; Ismaili, H; Ababou, A; Cherrah, Y; Quessar, A El
Abstract : Background: The overall prevalence of intracranial aneurysm is thought to be between 0.5 to 6% of population, based on angiographic study and autopsies. The frequency of detection and treatment of these aneurysms has increased due to the greater use of non-invasive diagnostic imaging techniques. Purpose: To demonstrate the cost of care by embolization of intracranial aneurysm and to understand relation between the cost and clinical patient parameters. Materials and Methods: Between January 2010 and April 2012 48 patients were treated by embolization of cerebral aneurysms. The cost of pharmaceutical products (drugs and medical devices) was assessed by using the micro-costing method that takes into account all direct costs and the overall cost of care was calculated using data from the hospital's information system. Results: In total, 48 patients were treated, mean age 52.4 ± 12.5 years. The sex ratio M/F = 0.71. 26 patients were covered by health insurance (52.2%). The median overall stay within 10 days [5–11] in ICU was 1 day [1 to 2] and in the medical unit was 6 days [3 to 9.75]. The overall average cost of treatment was €9, 697.8, varying from €4, 784.3 to €32, 172.3. The cost of pharmaceutical products was on average 57.6% of the overall cost. While the average cost of consumables was €5, 612.4 with a range of €2, 499.1 to €16, 370.8. Length of stay does not influence the overall cost of care, but the cost is influenced by the amount of embolization material. Conclusions: The cost of pharmaceutical products in the endovascular treatment of intracranial aneurysms remains high and represents a major handicap for the development of this technique in countries with low coverage by health insurance. As we mentioned before, this latter overall cost is especially influenced by number of embolization materials and number of aneurysms. No conflict of interest.